Income Earner Status and Couple Type and Its Impact on Marital Satisfaction - Ratnasari, Yudiana; Fatheya, Fath (UI Scholars Hub, 2022)
The rise of opportunities for females to work outside household settings in Indonesia has changed the division of traditional roles and responsibilities among married couples and thus may affect the quality of marital relationships. This study aims to observe how income earner status (single or dual earner) within families and couple type play roles in marital satisfaction. The participants comprised 224 spousal couples who are analyzed individually and together to categorize couple types measured using the Relational Dimension Instrument and Couple Satisfaction Index. Results indicate that for income earner status, no significant predominant effect on marital satisfaction was observed. The average marital satisfaction scores between couples with single- and dual-income statuses were insignificantly different, suggesting that dual- or single-income status does not have a direct effect on marital satisfaction. Based on couple type, traditional and separated types showed the highest marital satisfaction mean scores and lowest marital satisfaction scores among other types, respectively. These results reveal that interdependence and conflict resolution communication are important aspects in determining marital satisfaction levels among the Indonesian couples who participated in this study.